The Effect of Industrial Work Practices, Work Skills, and Work Motivation on the Work Readiness of State Vocational School Students Department DPIB in Makassar City - Luthfi FIkri Pratama Putra Lukman; Mithen Lululangi; Taufiq Natsir (FKIP - Universitas Riau, 2026)
This research is motivated by the suboptimal work readiness of vocational high school students, especially those majoring in Building Modeling and Information Design (DPIB) in Makassar City. This condition is influenced by the implementation of Industrial Work Practices, work skills, and student work motivation.A quantitative approach with the ex post facto method was used. The population consisted of 100 grade XII DPIB students from public high schools/vocational high schools, with 88 students selected as samples using the Slovin formula and proportional random sampling. Data were collected through observation, documentation, and questionnaires. Data analysis included descriptive analysis, prerequisite tests, and regression analysis. The results of the study show that (1) Industrial work practice has a positive effect on work readiness with a contribution of 56.4%, (2) Work skills have a positive effect on work readiness with a contribution of 44.6%, (3) Work motivation has a positive effect on work readiness with a contribution of 59.1%, (4) simultaneously, the three variables have a positive effect on work readiness with a combined contribution of 67.0%. This study concludes that industrial work practice, work skills, and work motivation have a positive effect on work readiness, with work motivation as the most dominant variable.